Dampak Literasi Digital Keyakinan Diri Dan Harapan Pendapatan Terhadap Intensi Berwirausaha Digital Pada Umkm Kecamatan Sumbawa - Laila Arbiah Fajriana; Muhammad Nur Fietroh (Advantage: Journal of Management and Business, 2023)
This study aims to analyze and examine the influence of digital literacy, self-efficacy and income expectations on the interest in digital entrepreneurship in MSMEs in the Sumbawa sub-district. This research uses quantitative methods. Determined the sample in this study using the Paul Leddy formula and obtained 100 research subjects through non-probability sampling technique with the purposive sampling method. The data analysis tool used SPSS 26. The results of the analysis in this study indicate that digital literacy, efficacy and income expectations partially have a positive and significant effect on digital entrepreneurship interest in MSMEs in Sumbawa District.